Cell polarity 1 : biological role and basic mechanisms - Ebnet, Klaus (Springer International Publishing Imprint: Springer, 2015)
This work provides a state-of-the art overview on the most relevant aspects of cell polarity. Volume 1 addresses cell polarity and cell migration (front-rear polarity), cell polarity and barrier formation (apico-basal polarity) and neuronal polarity. It particularly focuses on cell polarity at the molecular level and the underlying molecular mechanisms. It also elaborates the common principles and mechanisms that regulate cellular polarization in different cell types and contexts. Both volumes are intended for professors, group leaders and researchers in cell biology as well as medical professionals in the fields of anatomy, cell biology, physiology, pathology and tumor biology.